Arab Proper Nouns between Staticity and Significance: An Approach in Light of the Foundations of Nominality - Al-Basala, Aida bint Saeed (Arts for Linguistic & Literary Studies, 2024)
The research endeavors to explore the essence of proper nouns in Arabic, delving into their inherent staticity and their significance, within the framework of nominality. It comprises an introduction, a preface, and five sections. The sections respectively discussed the following issues: the analysis of linguistic perspectives on the staticity and significance of proper nouns, examination of the evolution of significance in proper names from selection to ascension, exploration of emblematic symbols in Arab cultural heritage, consideration of the naming of locations, and finally, connotation suggestibility into the evocative potential of proper names in literary contexts. The findings underscore the profound insights of scholars regarding the essence of proper nouns, depicting them as vessels imbued with rich connotations throughout individuals' lives. Naming practices reflect a spectrum of influences including personal taste, aesthetics, history, culture, and ideology, thereby unveiling the identity, mindset, cultural affiliation, and temporal context of the namer.